Columbo Season 3 - Falk, Peter 1927-2011. (Universal City, CA : Universal Studios Home Entertainment, 2012)
From the halls of Congress to the halls of academia, this set includes all episodes of the classic third season.
[Disc 1.] Lovely but lethal -- Any old port in a storm ; [disc 2.] Candidate for crime -- Double exposure ; [disc 3.] Publish or perish -- Mind over mayhem -- Murder is a parlor game ; [disc 4.] Swan song -- A friend in deed.
Originally broadcast on television.
Bonus material: Disc 3 has one episode from the TV show Mrs. Columbo.
Peter Falk.
Not rated.
105429
Keywords: Columbo, Lieutenant (Fictitious character) -- Drama; Detective and mystery plays; Criminal investigation -- Drama; Video recording; Los Angeles (Calif.) -- Drama